2017
DOI: 10.1016/j.rmed.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of Pseudomonas aeruginosa colonization in patients with Primary Ciliary Dyskinesia

Abstract: Lung PA colonization in PCD is associated with more severe disease as shown by the FEV and CT score. However, the magnitude of decline in pulmonary function was similar in colonized and non-colonized PCD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 27 publications
4
44
0
2
Order By: Relevance
“…About the results of microbiology of sputum, they resulted in agreement with the results of other studies that reported Haemophilus influentiae and Pseudomonas aeruginosa as the most common pathogens in PCD [12,18].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…About the results of microbiology of sputum, they resulted in agreement with the results of other studies that reported Haemophilus influentiae and Pseudomonas aeruginosa as the most common pathogens in PCD [12,18].…”
Section: Discussionsupporting
confidence: 88%
“…Considering both pediatric and adult PCD patients, Cohen Cymberknoh [18] also reported an overall prevalence of PA colonization of about 27%; those colonized with PA were older and diagnosed at a later age. Similarly, we observed that chronic PA lung colonization in PCD was associated with older age.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We carried out univariate analyses to evaluate the association between various clinical parameters and the total number of coughs/h and cough epochs/h using negative binomial mixed models [19]. Little evidence exists about the associations of clinical parameters with advanced lung disease in PCD patients [20, 21]. In contrast, several parameters are associated with worse course of lung disease or increased mortality in CF patients [22-26].…”
Section: Methodsmentioning
confidence: 99%